The Influence of Corporate Governance and Gender Board Diversity on Climate Change Disclosure: Evidence from Indonesian Listed Companies - Dea Tiara Moonalisa Butar Butar; Christofer Paskah De La Cruz; Iskandar Itan (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Climate change disclosure is a crucial aspect of corporate sustainability, reflecting how firms address environmental risks and communicate their climate-related initiatives to stakeholders. This study aims to examine the relationship between board gender diversity, corporate governance, and the extent of climate change disclosure among publicly traded companies in Indonesia. Using a quantitative research design, data were collected from companies listed on the Indonesia Stock Exchange from 2019 to 2023, and regression analysis was conducted to assess the impact of board gender composition, board size, board independence, and other governance structures on climate-related disclosures, with information sourced from sustainability reports and annual reports. The results reveal that board gender diversity, particularly independent female directors, and larger board size positively and significantly influence the level of climate change disclosure, whereas financial performance measures such as firm size, return on assets, return on equity, and leverage do not exhibit significant effects. These findings indicate that governance and structural factors, rather than purely financial metrics, drive voluntary environmental transparency. This study highlights the importance of promoting gender-diverse boards and strengthening corporate governance to enhance climate-related reporting, improve stakeholder trust, and support sustainable business practices aligned with global environmental goals.